Indo-Muslim cultures in transition - Patel, Alka.; Leonard, Karen Isaksen, 1939-; Indo-Muslim Cultures in Transition (2008 : Irvine, Calif.) (Leiden ; Boston : Brill, 2012)
The authors in this volume analyze the rich layers of circulation and exchange of art, architecture, and literature within South Asia from the sixteenth through the twentieth centuries, focusing on the interaction of Muslims and Islamic traditions ...
Papers originally presented at a conference held at the University of California, Irvine, also titled Indo-Muslim Cultures in Transition, from Oct. 31 to Nov. 2, 2008.
Includes bibliographical references and index.
Print version record.
Keywords: India -- Civilization -- Islamic influences -- Congresses; India -- Civilization -- 1200-1765 -- Congresses; Muslims -- India -- History -- Congresses; Islam -- India -- History -- Congresses; Mogul Empire -- History -- Congresses; SOCIAL SCIENCE -- Discrimination & Race Relations; SOCIAL SCIENCE -- Minority Studies; Civilization; Civilization -- Islamic influences; Islam; Muslims; India; India -- Mogul Empire; 1200 - 1765; Electronic books; Conference papers and proceedings; History; Electronic books